IDENTIFIKASI TINGKAT KEMAMPUAN SISWA DALAM REPRESENTASI FREE BODY DIAGRAMS UNTUK MENYELESAIKAN SOAL FISIKA PADA MATERI HUKUM NEWTON - Suratno, Fariska Anindrasari; Hatibe , Amiruddin (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aimed to determine and identify the level of students' ability in the representation of Free Body Diagrams (FBD) to solve physics problems on Newton's law material. This research was a qualitative descriptive study. This research was conducted at Man Insan Cendekia Palu City in the 2019/2020 academic year. The subjects in this study were students of class X IPA Asy-Syams Man Insan Cendekia Palu City, totaling 16 people. The respondents of this study were 6 people based on high, medium, and low categories. The research instrument consisted of a written test and an interview test. The results showed that the level of ability to draw FBD students of class X IPA Asy-Syams Man Insan Cendekia Palu City generally entered the level of needs improvement for questions number 1, 2, and 3 with an average percentage of 83.33% respectively. , 66.67%, and 66.67%. As for the question number 4 obtained a percentage of 50% of students entered at an inadequate level in drawing FBD on Newton's law material.